Direito ao recurso no processo penal : o duplo grau de jurisdição como garantia exclusiva do imputado - Mendes, Tiago Bunning (2018)
This work intends to investigate the origin, current scenario of the appeals and the double degree of jurisdiction in criminal procedure and, in order to demonstrate a continuity in the unitary treatment of the appealing system in civil and criminal proceedings, resulting from the General Theory of Impugnation. Thus, it will be proposed the adoption of concepts and elements specifically related to the criminal process and that will lead to a review of the ideas concerning to the judicial nature of appeals, classification, effects and legitimacy to appeal, aiming the rupture of the appealing bilaterality. We will also face the argument that the appeals are considered delaying tactics if analyzing the data published by CNJ referring to proceedings and appeals in process in STF. Therefore, the main discussion of this work is the violation of the double degree of jurisdiction that occurs by the modification of a absolutory sentence in result of a appeal brought by the prosecutor. Because of this, the fundaments and contents of the double degree of jurisdiction will be reviewed, granting exclusive protection to the accused, in order to achieve double compliance in criminal matters and protecting the presumption of innocence. From this we will demonstrate that there are no arguments to add limits to the double degree of jurisdiction. Finally, we will present alternatives that could limit accusatory appealing in order to stablish a compatible system with the guarantee of the double degree of jurisdiction.